Indoctrination and coercion in agent motivation: Evidence from Nazi Germany. (May 2018) - Miller, Charles; Barber, Benjamin; Bakar, Shuvo
How do principals combine indoctrination and coercion to motivate their agents? Based on previous literature, we argue that indoctrination on the one hand and coercion on the other are substitutes in agent motivation—more of one requires less of the other. But measuring this substitution effect is hard since individuals often self-select into ideological organizations and have incentives to claim insincerely to be ideologically motivated. Using a novel dataset of wartime behavior contained in a large sample of World War II German service records, we present a solution to these problems. We find convincing evidence to support our theory—the German army was able to induce similar effort levels from soldiers who had and had not been in the Hitler Youth, though Hitler Youth alumni required fewer punishments.